SUBALTERN DAN NASIONALISME DALAM NOVEL NYAI DASIMA (1960) KARYA S. M. ARDAN - HY, Mcfulvia (Adabiyyāt: Jurnal Bahasa dan Sastra, 2021)
This paper analyzes new meanings as the results of the reception written by S.M. Ardan in Nyai Dasima, which is known to have a central meaning, generally refers to the colonial efforts to liberate Nyai Dasima from colonialism. Recognized as a victim of colonial social structures, Nyai Dasima yearns for liberation by restoring her position, maintaining her identity and self-respect by rebelling against colonial oppression based on indigenous woman nationalism. The theory used in this paper is Gayatri Spivak's critical reading of the subaltern, which refers to “third world women” who are considered unable to speak or have a voice. This analytical method is the deconstruction method to find what Spivak calls “cognitive failure”. The analysis of this paper found that the rebellion and resistance carried out by Nyai Dasima represent an act of liberation from the shackles of colonialism which suppresses subaltern groups, especially women. However, it was found that the exemption offered to Nyai Dasima was parole which in no way refers to a sovereign and privileged subject.